2023
DOI: 10.3389/fchem.2023.1227288
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and structural analysis of fucomannogalactan and β-1,6-glucan from Grifola frondosa mycelium

Jie Geng,
Guining Wang,
Jiao Guo
et al.

Abstract: Introduction: Polysaccharides, key components present in Grifola frondosa, can be divided into those derived from fruiting bodies, mycelium, and fermentation broth based on their source. The structure of G. frondosa fruiting body-derived polysaccharides has been fully characterized. However, the structure of G. frondosa mycelium-derived polysaccharides remains to be elucidated.Methods: In this study, we obtained mycelia from G. frondosa by liquid fermentation and extracted them with water and alkaline solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this study, we investigated the inhibition of inflammation in AD and the underlying mechanisms of G. frondosa , which has a wide range of therapeutic activities such as immunomodulatory, antioxidative, and anti-inflammatory properties [ 12 21 22 ]. Many studies reported that G. frondosa harbors essential bioactive constituents, including β-glucans, with a relatively high content [ 23 24 25 ]. In addition, the application of β-glucans has been shown to result in significant improvements in the clinical symptoms of AD, particularly in the notable alleviation of pruritus in the treated half of the patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the inhibition of inflammation in AD and the underlying mechanisms of G. frondosa , which has a wide range of therapeutic activities such as immunomodulatory, antioxidative, and anti-inflammatory properties [ 12 21 22 ]. Many studies reported that G. frondosa harbors essential bioactive constituents, including β-glucans, with a relatively high content [ 23 24 25 ]. In addition, the application of β-glucans has been shown to result in significant improvements in the clinical symptoms of AD, particularly in the notable alleviation of pruritus in the treated half of the patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, hydrophobic bonding dominates in a certain temperature range, leading to the final phase transition from sol to gel. It should be noted that for additives to induce the sol-gel phase transition, a crucial requirement is a substantial alteration in the solubility of polysaccharides in water due to variations in external factors such as temperature, pH, and ionic strength (Geng et al 2023). This change is the primary driving force behind the phase transition in polysaccharide solution systems.…”
Section: Additive-modified Polysaccharidementioning
confidence: 99%
“…Avermectin fermentation residue (AFR) is a byproduct of the fermentation process for producing avermectin, and the annual production of this residue is about 40,000 tons (Cai et al, 2019). AFR mainly consists of mycelial cells, unutilized culture media, microbial metabolites, and residual avermectin (Geng et al, 2023). The residual avermectin presents the potential risks of the spread of antibiotic resistance in organisms (Ding et al, 2019), which seriously threatens the ecosystem and human health (Barra Caracciolo et al, 2011;Huang et al, 2017;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%